TINJAUAN KETEPATAN PUKULAN SMASH DALAM PERMAINAN BULUTANGKIS PEMAIN PB KOTO PERIANG KECAMATAN KAYU ARO KABUPATEN KERINCI - Tria Bundala; Roki Putra; Jonika Trishandra (EDU RESEARCH, 2024)
Review of the smash accuracy of PB badminton players. Koto Periang still varies. This study aims to determine the accuracy of smash shots of badminton players PB. Koto Periang. This type of research uses quantitative descriptive research method which is a method that aims to create a picture or descriptive of a situation objectively using tests, measurements and numbers, starting from data collection, interpretation of the data and appearance and results. The research population is players who actively participate in PB badminton training. Koto Periang which amounted to 17 players who were taken using total sampling technique, so it is called population research. The instrument used is the badminton smash accuracy test from Saleh Anasir (2010: 27) with a validity of 0.926 from the round robin tournament criterion and a reliability of 0.90 from the test-retest. Data review uses quantitative descriptive review which is poured using the percentage formula. The results showed that the accuracy of smash shots of badminton players PB. Koto Periang is in the ‘very less’ category by 5.88% (1 player), ‘less’ by 29.41% (5 players), ‘enough’ by 29.41% (5 players), ‘good’ by 29.41% (5 players), and ‘very good’ by 5.88% (1 player).